Determinants of Egyptian exports (Journal of Informatics Education and Research, 2025)
Exports are a crucial factor in the development of any country's economy. However, the factors that determine the volume and destination of exports are still not fully understood. This study aims to identify the determinants of Egyptian exports from 2000 to 2022, using the gravity model for estimation. According to the Fixed Effects Model, Egyptian exports are positively affected by GDP and negatively by population. Geographical and cultural factors do not affect exports. On the contrary, Egyptian exports are positively affected by concluding free trade agreements (FTAs). Corruption acts as a constraint on Egyptian exports, but the high level of corruption in its trading partner enhances exports. This counterintuitive result warrants further scrutiny and investigation.